2020
DOI: 10.1371/journal.pone.0240478
|View full text |Cite
|
Sign up to set email alerts
|

Kahweol activates the Nrf2/HO-1 pathway by decreasing Keap1 expression independently of p62 and autophagy pathways

Abstract: Kahweol is a diterpene found in coffee beans and unfiltered coffee drinks. Several studies have demonstrated that kahweol induces the nuclear factor erythroid-2 related factor 2/ hemeoxygenase-1 (Nrf2/HO-1) pathway; however, the mechanisms involved are currently unknown. Kelch-like ECH-associated protein 1 (Keap1) is a major regulator of Nrf2 expression and is degraded mostly by autophagy. The p62 protein enhances binding to Keap1 and contributes to the activation of Nrf2. Here, we examined the role of Keap1 r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…3 ): modification of Kelch-like ECH-associated protein 1 (KEAP1; regulates proteasomal degradation of NRF2), which is inactivated when its sensor cysteines form adducts with electrophiles or when they are oxidized to disulfides; disruption of the interaction between β-transducin repeat-containing protein (βTrCP; ubiquitylates NRF2 for degradation) and NRF2, via oxidative inhibition of the axis of glycogen synthase kinase 3β (GSK3β)–NRF2 phosphorylation at the Neh6 domain–βTrCP; KEAP1 sequestration by p62; de novo synthesis of NRF2 that escapes degradation by inactivated KEAP1 (ref. 181 ); and BACH1 inhibitors that reduce NRF2 suppression by BACH1, including agents that inhibit BACH1 translation 182 and promote BACH1 degradation 183 .
Fig.
…”
Section: Antioxidant Therapeutic Strategiesmentioning
confidence: 99%
“…3 ): modification of Kelch-like ECH-associated protein 1 (KEAP1; regulates proteasomal degradation of NRF2), which is inactivated when its sensor cysteines form adducts with electrophiles or when they are oxidized to disulfides; disruption of the interaction between β-transducin repeat-containing protein (βTrCP; ubiquitylates NRF2 for degradation) and NRF2, via oxidative inhibition of the axis of glycogen synthase kinase 3β (GSK3β)–NRF2 phosphorylation at the Neh6 domain–βTrCP; KEAP1 sequestration by p62; de novo synthesis of NRF2 that escapes degradation by inactivated KEAP1 (ref. 181 ); and BACH1 inhibitors that reduce NRF2 suppression by BACH1, including agents that inhibit BACH1 translation 182 and promote BACH1 degradation 183 .
Fig.
…”
Section: Antioxidant Therapeutic Strategiesmentioning
confidence: 99%
“…Studies suggest that CF and KW may condition health-promoting effects via Nrf2, but unlike caffeine, without exerting influence on cAMP levels. There is no known cAMP modulation by CF or KW [51][52][53].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, animal studies have revealed that cobalt protoporphyrin-induced HO-1 or its upstream regulatory gene Nrf2 is effective against hepatitis C and B viruses, dengue virus, Zika virus, Ebola virus, human immunodeficiency virus, and human respiratory syncytial virus (Hooper 2020 ; Wu et al 2019a ). HO-1 expression is essentially regulated by the Keap1/Nrf2 system at the transcriptional level (Seo et al 2020 ).…”
Section: Nrf2’s Anti-viral Roles In Covid-19mentioning
confidence: 99%